A contingent approach to country-of-origin effects on foreign products evaluation: Interaction of facets of country image with product classes. Issue 5 (October 2016) - Costa, Camila; Carneiro, Jorge; Goldszmidt, Rafael
Highlights: We examine interaction effects between facets of country image and product classes. We found that the sizes of the effects of CoI facets vary across product classes. Our conceptual model of CoI increases meaningfulness and accuracy in prediction. Abstract: This study investigates the effect of country-of-origin image on consumers' evaluations of foreign products and disaggregates the effects across facets of country image and across product classes. We disentangle country image into cognitive and affective dimensions, and additionally disaggregate the cognitive dimension into geographic and human aspects. We posit that country-of-origin effects will vary across distinct facets of country image and that the effect of each facet of country image will vary across different classes of products. By means of an online survey, data were collected from French consumers regarding their perceptions of cognitive and affective aspects of two countries – Brazil and Germany – and their evaluation of three product classes – utilitarian nature-based, utilitarian industrialized and hedonic industrialized – which were represented respectively by fruits, home appliances and clothes. Empirical results partially corroborate the hypothesized contingent impacts.